The Relationship between Risk Factors and Microalbumiuria for Ischaemic Stroke : A Case Control Study (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: Epidemiologic studies have reported that microalbuminuria is a risk factor for stroke in men and a limited case control study found that the highest quintile of microalbuminuria values was associated with 13 fold increased risk for stroke. The goal of this study is designed to determine its relationship to risk factors for ischemic stroke. Materials and Methods: It was a prospective observational study conducted in the Department of Neurology, Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh. Fifty consecutive patients with ischemic stroke with at least two risk factors who fulfilled the inclusion criteria of case were confirmed by CT or MRI. Equal number of controls same ages without stroke who had at least two risk factors were compared with the case group. The patients were assessed clinically with structured questionnaire including blood pressure, height and weight, and monitoring blood glucose and microalbuminuria. Results: Microalbuminuria was found 58.0% in patients with ischemic stroke. Patients who had diabetes mellitus will have 13.86 times the risk for developing microalbuminuria (p